Designing Parking System-Based Vb.Net and MySQL Using Radio Frequency and Identification (RFID) - Adi Fajaryanto Cobantoro; Fery Grahanda Anugra (VOLT : Jurnal Ilmiah Pendidikan Teknik Elektro, 2017)
Parking system has become a significant need for a university. A good parking system is used to ensure the user's vehicle safety. The current parking system applied in Universitas Muhammadiyah Ponorogo is still manual. Instruments of the study are observation, interview, and software development method used is waterfall method. This study has designed a parking application using RFID technology that can show users to empty parking locations so that customers can find vacant parking locations quickly and reduce queuing processes. The identification process is done when a customer enters the parking lot. Media used is in the form of RFID card. With parking applications using Radio Frequency and Identification (RFID), it changes the manual parking system into a more effective and efficient parking system.